Entrepreneurial Orientation for Enhancement of Marketing Performance - Heng, Lie; Afifah, Nur (International Review of Management and Marketing, 2020)
The purpose of this research is to fill a research gap in entrepreneurial orientation and marketing performance by using differentiation strategy and network capabilities. The research conducted by involving 135 creative SME categorized in handcraft, fashion, and printing and design in Pontianak, West Borneo, Indonesia. Five hypotheses are being developed and tested. For data analysis this research using statistic software called SEM AMOS 24. The findings of the research, it emphasizes the importance of supported differentiation strategy by entrepreneurial orientation in improving marketing performance. Furthermore, it confirms that network capabilities are a predictor of marketing performance. Keywords: Entrepreneurial orientation, differentiation strategy, Network capability, Marketing performance, Indonesia. JEL Classifications: L26, M31, L14, L25 DOI: https://doi.org/10.32479/irmm.9670